Dietary intake misreport: what we know - Magalhães,Vânia (2019)
Nutritional epidemiological studies are essential to the development of appropriate public health programs and food policies. However, the relation between nutrient intake and health outcomes might be affected by dietary intake misreport. The purpose of this study was to review the phenomenon of dietary intake misreport, including the existing evaluation methods, its implications, its prevalence and its associated factors. A bibliographic research was carried out. The reference method for studying dietary misreport is Doubly Labelled Water, by comparison of reported energy intake with total energy expenditure. Since it presents limitations of use in large epidemiological studies, alternative methods were described, some of which are univariate and others are multivariate. Few studies take into account under- and over-reporters and those who account differ on the way of identifying misreporters, which makes interpretations and comparisons difficult. Regardless the method, in each study, a consideration should be addressed to misreport prevalence, misreporters’ characteristics and how under and over-report affects nutrient analysis.